PELAKSANAAN PENANGGUHAN PENAHANAN TANPA JAMINAN UANG ATAU ORANG DI KEPOLISIAN RESOR KARIMUN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Suspension of detention is an act by removing a suspect or defendant from detention before the time limit for his detention ends. In the suspension of detention, the time limit or period of detention is still valid and justified according to the law, but the implementation is suspended or stopped after the suspension requirements are met by the suspect or defendant and or other people who act to guarantee the suspension of detention.The purpose of this study, is to determine the implementation of the suspension of detention without a guarantee of money or people in the Karimun Resort Police, and to find out the basic considerations of the Karimun Resort Police in providing suspension of detention without guarantee of money or people against the suspect. Whereas in the Criminal Procedure Article 1 point 21. The matter that is considered necessary to detain a suspect has been regulated in Article 21 paragraph 1 of the Criminal Procedure Code.This type of research is a sociological legal research, because in this study the authors directly conduct research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was carried out in the Karimun District Police Legal Area, while the population and sample were all parties related to the problems examined in this study.The suspension of detention is accompanied by a guarantee that it can be accounted for in an effort to minimize prisoners fleeing. The procedure for implementing the guarantee is regulated in Article 35 and Article 36 of Government Regulation No. 27 of 1983 concerning the Implementation of the Criminal Procedure Code, namely a guarantee of suspension in the form of money and a guarantee of suspension in the form of persons. Based on the Minister of Justice's Decree Number 14-PW.07.03 / 1983 regarding Additional Guidelines for the Implementation of the Criminal Procedure Code states that in the event that there is a request to suspend the detention granted, an agreement is held between the competent official in accordance with the level of examination with the suspect or advisor the law along with the conditions.To the police in the implementation of the suspension of detention at the level of investigation carried out by investigators need to be done optimally by setting guarantees so as not to neglect the conditions imposed and in conducting investigations can improve better coordination of all parties involved.Keywords: Suspension, Detention, Money Guarantee or People